Highly chemo-, enantio-, and diastereoselective [4 + 2] cycloaddition of 5H-thiazol-4-ones with N-itaconimides - Qiu, Shuai; Tan, Choon-Hong; Jiang, Zhiyong (Beilstein Journal of Organic Chemistry, 2016)
A dipeptide-based urea-amide tertiary amine (DP-UAA) was shown to be an effective Brønsted base catalyst for the first asymmetric annulation reaction between 5H-thiazol-4-ones and N-itaconimides. High levels of enantioselectivity (up to 99% ee) and diastereoselectivity (>19:1 dr) were obtained for a series of spirocyclic 1,4-sulfur-bridged piperidinone-based succinimides.
Keywords: [4 + 2] annulation; asymmetric organocatalysis; dipeptide-based Brønsted bases; 5H-thiazol-4-ones; N-itaconimides